Respon Pertumbuhan Jagung Hibrida (Zea mays) Terhadap Sistem Olah Tanah dan Pengendalian Gulma - Chairuddin Chairuddin; Dewi Andriani; Rayhan Amadius Weihan; Putri Mustika Sari (Politeknik Pembangunan Pertanian Malang, 2023)
Corn is an alternative source of carbohydrates besides rice and wheat. Corn is used as feed in the livestock industry and various processed foods. BPS data for 2023 shows that corn production is decreasing, which has an impact on corn self-sufficiency and a lack of corn fulfillment for export needs. The research aims to determine the effect of interactions between soil processing systems and weed control on the growth and yield of hybrid corn plants. This research uses factorial RAK with interactions. The first factor is the tillage system with levels T0 (no tillage) and T1 (tillage). The second factor is weed control time with levels G0 (weed free), G1 (weeds controlled at 15 HST), G2 (weeds controlled at 35 HST), G3 (weeds controlled at 55 HST). The results showed that the tillage system and weed control time were significantly different in the test BNT 5%. However, the interaction not significantly different in the test BNT 5%. Corn plants with tillage (T1) and weed free (G0) showed the best growth and yield compared to other treatments in all observed variables.